Shackleton and the lost Antarctic expedition - Hoena, B. A.; Hoover, Dave 1955-; Barnett, Charles (Mankato, Minn. : Capstone Press, 2006)
In graphic novel format, tells the story of Antarctic explorer Ernest Shackleton and his failed attempt to cross the coldest and windiest continent on earth.
Includes bibliographical references
9 - 12 years
Keywords: Shackleton, Ernest Henry -- 1874-1922 -- Travel -- Antarctica; Endurance (Ship); Antarctica -- Discovery and exploration -- British